The Impact of E-Government System Policy on Employee Performance and its Influence on the Effectiveness of Public Services in the Regional Government of Pesawaran Regency - Rahayu, Mieke; Fadila, Kurnia; Purnomo, Ari (Jurnal Manajemen Teknologi, 2024)
Abstract. Implementing a government electronic system changes the work environment by improving efficiency, cooperation, data accuracy, flexibility, skill development, feedback systems, and customer service while lowering administrative costs. These adjustments, taken together, contribute to enhanced employee performance across a variety of parameters. As a result, it is vital to research how government electronic system rules affect staff performance, particularly public service efficacy. This study involves quantitative research methodologies, with data collected using a Google Form questionnaire emailed to the staff of the Pesawaran Regency Government Administration Office. After collecting 100 replies, the data were analyzed using the Partial Least Squares Path Modelling (PLS-PM) approach to evaluate the hypothesis. The study's findings show that government electronic systems policy has a major impact on staff performance, which in turn influences the effectiveness of public services. Keywords:  E-Government system; employee performance; public services; effectiveness, partial least squares    Abstrak. Penerapan sistem elektronik pemerintah mengubah lingkungan kerja dengan meningkatkan efisiensi, kerja sama, akurasi data, fleksibilitas, pengembangan keterampilan, sistem umpan balik, dan layanan pelanggan sekaligus menurunkan biaya administrasi. Penyesuaian ini, jika digabungkan, berkontribusi pada peningkatan kinerja pegawai di berbagai parameter. Oleh karena itu, penting untuk meneliti bagaimana aturan sistem elektronik pemerintah memengaruhi kinerja staf, khususnya efektivitas layanan publik. Penelitian ini melibatkan metodologi penelitian kuantitatif, dengan data yang dikumpulkan menggunakan kuesioner Google Form yang dikirim melalui email kepada staf Kantor Administrasi Pemerintah Kabupaten Pesawaran. Setelah mengumpulkan 100 balasan, data dianalisis menggunakan pendekatan Partial Least Squares Path Modelling (PLS-PM) untuk mengevaluasi hipotesis. Temuan penelitian menunjukkan bahwa kebijakan sistem elektronik pemerintah memiliki dampak besar pada kinerja staf, yang pada gilirannya memengaruhi efektivitas layanan publik.  Kata kunci: Sistem e-Government; kinerja pegawai; layanan publik; efektivitas, partial least squares